Survei Kepuasan Mahasiswa terhadap Pelaksanaan Pelatihan ESQ 165 pada Orientasi Studi dan Pengenalan Kampus (Ospek) STIKes PHI - Elwindra Elwindra; Diana Barsasella (Jurnal Persada Husada Indonesia, 2014)
Student Orientation (Ospek) implementation always filled by a series of violations in the form of violence is not only contrary to human rights, but also deny the noble goals of education to shape the nation's youth and leaders who are intelligent, intellectual, emotional, and spiritual. On this basis STIKes PHI and several other colleges make a paradigm shift in the implementation ospek to Emotional Spiritual Quotient (ESQ) training through an emotional and spiritual intelligence training. ESQ training Implementation Ospek during new student this would require an evaluation to assess the sustainability of the program and provide inputs for the following year. With this goal needs to be done customer satisfaction survey, which will measure the level of student satisfaction on the implementation of the ESQ training. This study uses customer satisfaction surveying through direct measurement of reported satisfaction, to elicit a response and feedback directly from customers. Research conducted by measuring the total sampling variables into 4 variables ESQ 165 training, namely: material, trainer, public facilities, and impact. The results showed that all student participants were satisfied , and religious differences do not affect the satisfaction of the participants, so it is advisable to continue the training program. Research also suggests several variables and factors that need to be maintained and continually improved service/performance, ie the variable material and training facilities, especially useful material and support of team ESQ 165.